MODELING THE IMPACT OF SUSTAINABLE TOURISM DIMENSIONS ON INTERNATIONAL TOURISM MARKET DIGITALIZATION WITH GREEN ECONOMY AS A MODERATOR - Poniasih Lelawatty; La Sudarman; Abel Haryanto; Sudarnice Sudarnice (Universitas Sains Al Qur'an, 2026)
Research on sustainable tourism focuses on ecotourism or digital technology adoption, with limited studies integrating the role of green economy principles as a moderating variable in the digitalization of the international tourism market. Therefore, this study aims to address this gap by analyzing the influence of natural resource conservation, local economic development, cultural appreciation, community participation, and green technology on tourism digitalization, while examining the moderating role of the green economy. The study was conducted at Batu Sori (Baubau City) and Waburi Park (South Buton Regency, Southeast Sulawesi), involving 150 tourists selected through purposive sampling. Data were analyzed using SEM-PLS. The results show that all independent variables have positive effects on the digitalization of the international tourism market. The green economy strengthens the influence of natural resource conservation, local economic development, and green technology, but does not significantly moderate the effects of local culture and community participation. Theoretically, this study contributes to an integrative model linking sustainable tourism, green economy, and digital tourism. Practically, the findings highlight the importance of aligning green economy policies, strengthening local economies, and adopting environmentally friendly technologies, with policy implications emphasizing digital capacity, infrastructure, and sustainable destination management strategies.